Cattle and sheep raising and millet growing in the Longshan age in central China: Stable isotope investigation at the Xinzhai site. (28th December 2016) - Dai, Lingling; Balasse, Marie; Yuan, Jing; Zhao, Chunqing; Hu, Yaowu; Vigne, Jean-Denis
Abstract: Previous bone collagen stable isotope analyses conducted on faunal remains from archaeological sites from the Late Neolithic (Longshan) to the Bronze Age (Xia dynasty) in the Central Plains of China have revealed that C4 plants – most probably cultivated millets – constituted a major part of cattle fodder and also contributed to sheep diet, although to a lower extent. In the present study, this difference between cattle and sheep diet management was investigated at the Xinzhai site (occupation phases 2 and 3, ca. 1800–1705 cal. BC), focusing on the seasonal scale through sequential δ 13 C and δ 18 O analysis in tooth enamel. This primary objective related to the reconstruction of Bronze Age husbandry practices required an effort in interpreting δ 18 O sequences recovered from cattle and sheep molars: potential difficulty in the identification of the seasonal cycle could rise, inherent to a specific climatic regime. This region of China is nowadays under the influence of the East-Asian summer monsoon, whose strength undergoes variability on the annual scale, but also did in the past on decadal to century scales. At Xinzhai, all sheep teeth and one deer tooth delivered δ 18 O sequences comparable to previously published sequences from locations were rainfall δ 18 O is temperature controlled (no monsoon influence), revealing minimal influence of the summer monsoon over these animals' lifetime. Some cattle teeth delivered sequences with bimodal distribution of δ 18 O values on the annual scale, potentially reflecting the influence of a summer monsoon. Such variability among domestic stock could relate to interannual/interdecadal variability in the monsoon intensity at the site location, or to differences in herding practices between sheep and cattle. Concomitant analysis of δ 13 C values in deer molars confirmed a surrounding wild environment dominated by C3 plants throughout the year, supporting the idea that a C4 signal in cattle and sheep diets resulted from feeding practices involving cultivated millets. Furthermore, sheep had access to millet in late summer time while cattle were constantly foddered throughout the year, to a very high extent. Given the annual growth cycle of millet, with late summer maturity, a year round provisioning to cattle would suppose constitution of fodder. Constant provisioning could also have required cattle to be kept by the settlement all year round, inducing less investment in cattle herding, but in return, a necessarily important input to sustain cattle diet requirements at the daily scale. This could in fine be connected to the privileged status for cattle in social or ritual related activities at Xinzhai.